(untitled) (Journal of Medicine, 2024)
Background: Psoriatic Arthritis (PsA) is a complex seronegative inflammatory arthritis associated with psoriasis, characterized by a wide range of clinical manifestations. This study aimed to explore the prevalence of PsA in arthritic patients along with associated demographic and clinical characteristics in a tertiary care setting in Bangladesh. Methods: This cross-sectional study was conducted at the Rheumatology Clinic of Dhaka Medical College Hospital over a period of 6 months from March 2018 to August 2018. A total of 600 arthritis patients underwent screening for PsA, with subsequent evaluations of confirmed cases based on the CASPAR criteria. Demographic and clinical characteristics were documented through face-to-face interviews and physical examination. For data collection, a pre-structured questionnaire was used. Disease activity was assessed using the DAPSA score. The study was conducted according to the ‘Declaration of Helsinki’. The statistical analysis was done with SPSS v-21. Results: The prevalence of PsA in arthritis patients was 5%. Age distribution of PsA showed a majority in between 30-39 years age group with a mean of 36.33±11.86 (SD). Slight female predominance was reported with a percentage of 53.3%. Almost three-fourths of study patients presented with a current diagnosis of psoriasis while the rest had a personal history or family history. A higher incidence (67.7%) of plaque psoriasis was observed followed by sebopsoriasis (20%) and for the rest of the patients, the type of psoriasis was unknown. The disease mostly involved multiple joints (90%), with ankle and metacarpal joints being the most commonly affected at 43.3% and 33.3%, respectively. Disease activity was high in the majority of the patients according to the DAPSA score, representing 53.34% of the patients, with the remainder exhibiting moderate to low disease activity. Conclusion: The study revealed a significant incidence of PsA among the arthritic population which indicates a pressing need for further extensive research on PsA across diverse populations. J MEDICINE 2024; 25: 35-40